Pengaruh Pembelajaran dengan Pendekatan TPACK terhadap Problem Solving Skill dan Kemandirian Belajar Siswa pada Mata Pelajaran Administrasi Infrastruktur Jaringan di SMK Negeri 1 Sepulu - Halimatu Sa’diyah; Sucipto Sucipto; Victor Maruli Tua L. Tobing (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
The purpose of this study is to explore the influence of the TPACK approach on problem solving skills and student learning independence in the Network Infrastructure Administration subject at SMK Negeri 1 Sepulu. The research methods used are quasi-experiments with Nonequivalent Control Group Design and mixed methods with Explanatory Design. Quantitative data were obtained from pretest and posttest, as well as questionnaires, which were analyzed using quantitative statistics. The results showed that the TPACK approach had a significant positive influence on both research variables, with the average value of problem solving skills and student learning independence higher in the experimental class than the control. Students also respond positively to learning with the TPACK approach. In conclusion, the TPACK approach is effective in improving students' problem-solving skills and learning independence. This research can be a reference for teachers to develop innovative learning in other subjects with similar characteristics.